Peningkatan Edukasi Pemeriksaan Payudara Sendiri (SADARI) Pada Remaja Putri di Kecamatan Medan Tuntungan - Suriati Lubis; Arva Rochmawati (Indonesian Journal Publisher, 2022)
Breast cancer is the cause of death of most women which is currently ranked second after cervical cancer among cancers that attack women. One effective way to detect breast cancer early is through breast self-examination (SADARI). This activity was carried out using a lecture method with presentation techniques, video playback, questions and answers and direct practice simulations packaged in the form of counseling. The media used are leaflets, laptop, LCD, MMT. This community service was carried out on Friday, January 13, 2023 which started at 11.30 WIB - finished at the Medan Tuntungan Subdistrict Area with the number of participants who participated in this counseling were 20 participants consisting of Teenage Girls in Medan Tuntungan Village. This community service activity is very effective in increasing knowledge for adolescent girls in conducting early detection of breast cancer through SADARI.